Interferometric dynamic displacement measurement using phase-modulated light along with stepwise control of operation point. (23rd October 2018) - Tanaka, Yosuke; Ueda, Kohei
Abstract: We propose the fiber-based interferometric measurement of tens-of-nanometer-scale dynamic displacement that uses phase-modulated reference light with stepwise control of the operation point of modulation (OPM). It requires neither the pre-adjustment of the OPM nor feedback control for the path-length difference of the interferometer. Quantitative evaluation of the system is performed by using a phase modulator as a sample to simulate mechanical vibration. The dynamic displacement for 100-kHz vibration with an amplitude of 19 nm is measured even when the fiber interferometer is intentionally perturbed, which confirms the effectiveness of the proposed method.